O paradigma dualista da hanseníase controle ou eliminação: o período crítico de 2000 a 2005 - Gonçalves, Aguinaldo; Mantellini, Glauca Gonçalves; Padovani, Carlos Roberto [UNESP] (My University, 2011)
One of the main tendencies of leprosy worldwide is the simultaneous action of non governmental organizations and official agencies operating eventual different strategies. This paper aims to contribute to such question focusing on some outstanding aspects of respective contemporary evolution. METHODS Application of bibliographic review and contents analysis techniques to primary data from a circumstancial set of open circulation specific publications. RESULTS Successive disagreements registered between both parts refer to the objective to be attained by the fight against the disease, if control or elimination. CONCLUSIONS New perspectives of jointed actions are being searched for now when priority on endemics control is more realistically assumed and social determination is been really considered.

INTRODUÇÃO: Uma das realidades atuais da hanseníase a nível do coletivo consiste na ação simultânea de órgãos oficiais e organizações não governamentais seguindo eventualmente estratégias diferenciadas. A presente comunicação visa contribuir para com tal questão, revendo alguns aspectos marcantes de respectiva evolução contemporânea. MÉTODOS Aplicação das técnicas de revisão bibliográfica e análise textual, enquanto metodologias conteudísticas, a dados primários de acervo circunstancial de publicações específicas em circulação aberta. RESULTADOS Os desencontros sucessivos demarcados entre ambos os setores explicitam-se no referente ao objetivo a ser atingido pela luta contra a doença, se seu controle ou sua eliminação. CONCLUSÕES Novas perspectivas de ações conjuntas são buscadas agora quando, mais realisticamente, se retoma a prioridade do controle da endemia e se contemplam, de fato, seus determinantes sociais.
Leprosy dual paradigm control or elimination: the critical period 2000-2005
Keywords: Leprosy; Control; Elimination; Hanseníase; Controle; Eliminação